大たい骨ＣＴスキャンによるじん性骨異栄養症患者の骨塩定量 - MARUMO F.; SATO M.; NAKAMURA M.; SHIMADA H.; SAKURAI K.; IWANAMI S. (Jinko Zoki, 1984)
The corrected CT numbers of the lateral condylus of femoral bone obtained by simultaneous scanning of the femoral bones and the artifitial references, in undialyzed and dialyzed patients were significantly decreased. The corrected CT numbers of mid-femoral bone in dialyzed patients were negatively correlated with the duration of dialysis. Ca contents in bone measured by the neutron activation analysis were decreased in both undialyzed and dialyzed patients. The present study suggests that the non-invasive method using CT scan is useful tool for measurement of bone mineral contents in patients with renal osteodystrophy. 腎性骨異栄養症の際の非観血的骨塩量測定には, 従来X線撮影あるいは光子吸収法が用いられているが, 精度および再現性について十分とはいいがたい。われわれは, 非観血的測定法としてCTを用い, 次の成績を得た。1. 大腿中央部及外顆部をそれに模したファントームと同時にCT撮影することにより, 精度及再現性において満足すべきCT値を得た。2. 大腿外顆部較正CT値は, 非透析群, 透析群において有意に低下していた。3. 血液透析群の大腿中央部較正CT値は, 透析期間と有意の負の相関を示した。4. 非破壊放射化分析法によって得られた成績では, 非透析, 透析群の骨中カルシウム含量は有意に低下していた。5. CTによって得られた非観血的成績はよく放射化分析法による成績と一致し, われわれのCTを用いた方法は極めて有用な手段であると考えられた。